STAGES OF FORMATION OF WRITING SKILLS IN STUDENTS IN ENGLISH LESSONS (Web of Teachers: Inderscience Research, 2025)
This article considers the stages of formation of writing skills in students. The main features of the development of writing skills from the graphic stage to the free writing stage and the role of teachers at each stage are identified. The article describes the activities of teachers aimed at developing writing skills in the English language, methods of organizing the educational process, and practical recommendations that will help students master writing skills.